The applicability of the ECHR in contested territories - Milanovic, Marko; Papić, Tatjana (Cambridge University Press, 2018)
This article examines the applicability of the European Convention for Human Rights (ECHR) when a State loses control over parts of its territory. It argues that the jurisprudence of the European Court for Human Rights, which insists on residual positive obligations based in sovereign title over territory, is problematic and needs to be rethought. The Court’s current approach is not only likely to provoke backlash, since it requires it to decide politically explosive questions of sovereign title, but does so for very little practical benefit for the protection of human rights. The article therefore explores more preferable alternatives.